ILLOCUTIONARY ACTS AND HATE SPEECH ON GUS MIFTAH - Fahmi, Ahmad Rosikhul; Ranu, Andarini; Khoiriyah, Hafi Dhotul (Ma Chung Press, 2025)
This study addresses three main questions: (1) What forms of illocutionary acts characterize hate speech in viral Instagram content involving religious figures? (2) How do these linguistic strategies polarize audience engagement in controversial religious discourse? (3) To what extent do platform mechanisms such as anonymity and algorithmic bias amplify toxicity? Through a qualitative netnographic analysis of five viral Instagram videos (late November–December 2023) featuring Gus Miftah and Ice Tea Seller three dominant hate speech themes emerge: religious-based attacks (52%), dehumanization (33%), and veiled threats (15%). Pragmatic analysis reveals that expressive illocutionary acts (60%—e.g., emotional outbursts) and directive acts (30%—e.g., demands for punishment) drive polarized engagement, with hate comments receiving three times as many likes and 35+ replies per thread compared to neutral comments. Platform dynamics exacerbate toxicity: 80% of hate comments come from anonymous accounts, while the algorithm promotes decontextualized clips, deepening ideological divisions. This study shows how linguistic aggression (micro-level) and platform architecture (macro-level) interact to normalize hate speech, offering actionable strategies for creators to counter hostility (e.g., context restoration) and platforms to prioritize ethical algorithms. By integrating linguistic theory with digital ethics, this study advances a framework for mitigating harm in Indonesia’s polarized social media landscape.